HAKIKAT TEORI DAN KONSEP ORGANISASI DALAM PERSPEKTIF ISLAM - Nikmatul Khoiriah; Nur Arfiyah Febriani (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study aims to explain the essence of organizational theory and concept from an Islamic perspective as a conceptual foundation for the development of Islamic educational management. In modern organizational theory, the emphasis on rationality, efficiency, and structure often neglects moral and spiritual dimensions, creating the need for a value-oriented alternative paradigm. Employing a qualitative approach through library research, this study analyzes classical to contemporary organizational theories and compares them with Islamic principles such as tawhid (unity of purpose), justice, trustworthiness (amanah), and consultation (shura). The findings indicate that Islamic organizational theory is value-oriented, humanistic, and spiritual, where every structure and decision within the organization is viewed as a collective trust and act of worship. The integration of knowledge and values within Islamic organizational theory produces a holistic paradigm that unites rationality, morality, and spirituality as the basis for just and ethical organizational management. This study contributes to strengthening the model of Islamic educational organizations that emphasize not only performance efficiency but also social benefit and divine blessing.